2017
DOI: 10.1057/s41599-017-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal perspectives of faculty and students on benefits and barriers to transdisciplinary graduate education: program assessment and institutional recommendations

Abstract: Addressing complex societal problems, such as childhood obesity, requires transdisciplinary (TD) approaches to reach effective solutions. However, TD doctoral training programs in academic settings are still relatively new, and little is known about the benefits and barriers of participation. This study sought to longitudinally assess benefits and barriers of a TD approach to doctoral education from the perspectives of students working towards a joint PhD/MPH degree and their faculty advisors. Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Currently, most educational efforts in obesity prevention and treatment occurs at the postdoctoral level in specialty programs such as those offered through Nutrition Obesity Research Centers (NORC) funded by the National Institute of Diabetes and Digestive and Kidney Diseases. There are a few doctoral level programs such as the Illinois Transdisciplinary Obesity Prevention Program (I-TOPP) (7) and the Pennsylvania State University Childhood Obesity Prevention Graduate Training Program funded by the United States Department of Agriculture, National Institute of Food and Agriculture. Rarer yet are interdisciplinary programs at the undergraduate level.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most educational efforts in obesity prevention and treatment occurs at the postdoctoral level in specialty programs such as those offered through Nutrition Obesity Research Centers (NORC) funded by the National Institute of Diabetes and Digestive and Kidney Diseases. There are a few doctoral level programs such as the Illinois Transdisciplinary Obesity Prevention Program (I-TOPP) (7) and the Pennsylvania State University Childhood Obesity Prevention Graduate Training Program funded by the United States Department of Agriculture, National Institute of Food and Agriculture. Rarer yet are interdisciplinary programs at the undergraduate level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, student advisor characteristics were not significantly different between the two groups ( Table 1 ), suggesting that advisor publication productivity, collaboration, and impact are not the main influence on student productivity, collaboration, and impact with regard to publication patterns. The greater impact and collaboration among TD students may be due to the nature of the I-TOPP program, described here and elsewhere [ 20 ], which fostered high support and high expectations, and provided highly structured programmatic support.…”
Section: Discussionmentioning
confidence: 99%
“…Specific challenges of transdisciplinary research programs were also well reported in the literature, particularly from the perspectives of faculty and program managers (Evans, 2015;Gillis et al, 2017;Vanasupa, McCormick, Stefanco, Herter, & McDonald, 2012). In the context of transdisciplinary graduate education, challenges included significant time investment, unclear expectations, limited reward systems for collaborative efforts, and unclear job prospects (Ciannelli et al, 2014;Keck et al, 2017). Enengel et al (2012) found that students in doctoral transdisciplinary research projects struggled in terms of "external dependencies and the ups and downs of social interaction and communication processes" (p. 116); the authors emphasized that the research progress was heavily dependent on the commitment and the schedules of numerous external actors.…”
Section: Preparing (Further) For Transdisciplinary Graduate Researchmentioning
confidence: 94%
“…While graduate students increasingly adopt transdisciplinary paradigms from training programs (Enengel et al, 2012;Keck et al, 2017), there is relatively little scholarship analyzing the roles that graduate students play and the ways in which their involvement can impact transdisciplinary collaborations. In this paper, we address this gap by critically analyzing and sharing our experiences as a team of graduate students and a community partner engaged in a transdisciplinary food security research project.…”
Section: What Our Experiences Mean For Transdisciplinarity and Action Researchmentioning
confidence: 99%
See 1 more Smart Citation